Enhancing urban governance through the implementation of local e-government: a case study of Kota Kinabalu City Hall (DBKK) - Mohd. Jaya, Silmy Safura; Jamaiudin, Norhaslinda (IIUM Press, International Islamic University Malaysia, 2017)
This case study examines the implementation of local e-Government services by Kota Kinabalu City Hall (DBKK), in terms of its implementation degree, customers’ satisfaction level and the relationship between its implementation and urban governance enhancement. The implementation of e-Government has significantly transformed public service delivery. The implementation of local e-Government by DBKK is part of the local authority’s initiative to improve Kota Kinabalu’s urban governance quality. Yet, since its implementation, the local e-Government service is plagued by one serious problem, which is the lack of online features in comparison to other local authorities. Research findings reveal that DBKK offers numerous online services, such as the online feedback form, e-Services, e-Compound and e-Tax. Overall, the public perceives the local e-Government services offered by DBKK as satisfactory and there is a positive relationship between the local e-Government implementation and urban governance improvement.